Detecção de proteínas imunorreagentes de Rickettsia parkeri cepa mata atlântica - Oliveira, Caroline Sobotyk de (2015)
The Brazilian spotted fever is an infectious disease transmitted by ticks to humans. The occurrence of Rickettsia rickettsii agent has been reported in Brazil since 1920 and is considered the main bacteria involved in Brazilian Spotted Fever. Since 2000, four other current species have been identified in the country, as follows: Rickettsia riphicephali, Rickettsia amblyommi, Rickettsia parkeri and Rickettsia felis. R. parkeri was first isolated in Amblyomma maculatum on the Gulf Coast of the United States in 1937, but until 2004 was considered as non-pathogenic agent, when was the first recognized case of spotted fever in humans caused by this species. Recently a new human rickettsial infection was reported to cause disease in São Paulo, being called Rickettsia parkeri Strain Atlantic Forest. This study aimed to detect and identify proteins with potential to stimulate the immune system of the host of this new strain described. Therefore, we performed total protein extraction R. parkeri Strain Atlantic Forest from infected VERO cell samples. The extracted proteins were fractionated by electrophoresis in polyacrylamide gel in the presence of sodium dodecyl sulfate (SDS-PAGE). The proteins were transferred to nitrocellulose membranes by semi-dry electrotransfer system and subjected to Western blot. Subsequently, the membrane was incubated with domestic rabbit hyperimmune serum against R. parkeri Strain Atlantic Forest (primary antibodies) followed by incubation with anti-rabbit IgG peroxidase-conjugated antibody (secondary antibody) to detect the primary antibodies bound to the proteins . Obtaining the hyperimmune rabbit serum was performed by experimental infection of R. parkeri Strain Atlantic Forest in domestic rabbit, intraperitoneally. After incubation, the disclosure of immunoreactive proteins was performed using a chromogenic substrate. 2 immunoreactants were detected proteins with more than 78 kDa (200 e 130 kDa) and 5 with less than 78 kDa. By comparing existing proteomic maps and the molecular weight of these proteins showed that, it is suggested that rOmpA (200 kDa) and rOmpB (130 kDa) are among the proteins detected and the remaining proteins found are members of the family of surface antigens cell (Sca - Surface cell antigen). However, one can not say that these proteins represent only reactive immunity to R. parkeri Strain Atlantic Forest, or that are homologous to other species. However, studies using the Modern Liquid Chromatography technique associated with mass spectrometry (LC/MS/MS) must be conducted for protein characterization. Preliminary results obtained in this study allowed further elucidation of protein profile of this agent, providing subsidies for the development of highly sensitive and specific diagnoses, as well as studies allow for the realization of a vaccine, as an alternative for the control and prevention of Brazilian Spotted Fever.